In vitro simulated digestion on the biostability of Hibiscus cannabinus L. seed extract - Wong, Yu Hua; Tan, Chin Ping; Long, Kamariah; Nyam, Kar Lin (Czech Academy of Agricultural Sciences, 2014)
We investigate the biostability of phenolic acids from a kenaf (Hibiscus cannabinus L.) seed extract using an in vitro model simulating the physicochemical (pH, temperature and bile salts) and biological (gastric and pancreatic enzymes) gastrointestinal conditions. Some of the antioxidants in the kenaf seed extract were not relatively stable in the intestinal phase of the gastrointestinal tracts. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity and total phenolic content (TPC) assays displayed similar trends as the biostability of phenolic acids, which decreased during the digestion process. The overall percentage loss of selected phenolic acids was 8.4–49.4% in the intestinal phase. For the overall in vitro digestion system, significant correlations between phenolic acids, total phenolic content (TPC) and antioxidant activity (DPPH) were obtained in all digestion phases with the exception of the gastric phase.